Narrativas de los estudiantes de un colegio y cómo significan su experiencia de aprendizaje de la educación sexual frente a las necesidades propias de su curso de vida - Camargo Benavides, María Paula; Rodríguez Torres, Brian Alexis (Universidad Antonio Nariño, 2023)
The purpose of this research is to understand how students signify their learning experience of sexual education in the face of the needs of their life course, as well as to know the experiences of the sexual education environment and how they have recognized it, meaning in their experiences personal